Pulmonary toxicity of nanoparticles in a lung-on-a-chip platform - Tan, Zou Wei (Nanyang Technological University, 2021)
The use of nanoparticles (NPs) started since last century. Due to their remarkable physical and chemical properties, NPs are used in a wide variety of applications, ranging from consumer products to biomedical applications. NPs are very small particles with sizes in the nano level. Due to the small size of NPs, they can be easily inhaled by humans. The NPs can reach and be deposited in the alveolar regions of human lungs. Studies have shown that many of the common NPs used are toxic. When these NPs are deposited and accumulated in human lungs for a long period of time, it can bring about pulmonary health issues like asthma and lung cancer. It is therefore crucial to investigate the effects of toxicity of commonly used NPs to study their toxicity on human lung cells. To test the toxicity of NPs, many studies use in vivo and in vitro models to determine nanotoxicity. However, both in vivo and in vitro models are not able to fully mimic a human lung microenvironment. A systematic assessment to study potential harmful effects of NPs on human lung cells is still lacking. This study aimed to evaluate the toxicity of commonly used metal oxide NPs like CuO, TiO2 and ZnO NPs by characterizing and conducting in vitro cytotoxicity tests of these NPs on lung epithelial cells (A549). A 3D human lung-on-a-chip in vitro co-culture model which mimics the structure of functions the airway interface of human lung was adapted. This 3D lung-on-a-chip model was used to investigate the morphological changes and cell viability of A549 cells and human lung fibroblasts (HLF) upon exposure to these NPs. The various findings and observations will be presented in this report.